The Effect of Chayote Extract (Sechium edule) On Blood Pressure in Pregnant Women with Hypertension - Fauziah, Nur Alfi; Hidajati, Kamilah; Soejoenoes, Ariawan (Indonesian Journal of Medicine, 2019)
Background: Increased blood pressure of pregnant women during pregnancy is one of the high risks during pregnancy which can lead to preeclampsia, eclampsia to maternal and infant mortality. One of the treatments recommended by pregnant women is to consume foods containing potassium and flavonoids, namely squash. This study aimed to determine the effect of squash pumpkin on changes in blood pressure of hypertensive mothers in pregnancy in the health center in Semarang City area.Subjects and Methods: This was an experimental study. The study was conducted at community health centers in Semarang, Central Java, from March to May 2018. A sample of 20 pregnant women who experienced hypertension in pregnancy was divided into two groups, control and treatment groups. The dependent variable was blood pressure. The independent variable was the extract of chayote. The data were analyzed by multiple linear regression.Results: There were differences in systolic blood pressure before and after the administration of squash extract (p<0.001). There are differences in Diastolic blood pressure before and after the administration of squash extract (p <0.001).Conclusion: Consuming chayote can make an effort to help lower blood pressure in pregnant women with hypertension. Keywords: flavonoids, hypertension in pregnancy, potassium, squash, blood pressure. Correspondence: Nur Alfi Fauziah. Postgraduate Midwifery Program, School of Health Polytechnics. Jl. Tirto Agung, Pedalangan, Banyumanik, Semarang City, 50268, Central Java, Indonesia. Email: nuralfifauziah24@yahoo.com.Indonesian Journal of Medicine (2019), 4(3): 266-277https://doi.org/10.26911/theijmed.2019.04.03.10